2016
DOI: 10.1177/0003702816681012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Tomato Ripening Based on Carotenoid Raman Spectroscopy: Experimental Versus Kinetic Model

Abstract: This work reports on a combined experimental and theoretical investigation on the carotenoid Raman signal in several tomato fruits during their postharvest time evolution and ripening. Both resonant (180°) backscattering and polarized (90°) Raman scattering were used to monitor the most prominent bands of carotenoid (lycopene and β-carotene) evolution in different tomato varieties. Relevant findings of the present investigations were that while the depolarization ratio of the ν band hardly changed with time, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Martin et al [ 85 ] developed a tomato ripening model based on vibrational bands of carotenoids in Raman spectra. Tomato fruit during the growth phase and during the post-harvest ripening stage were analysed using a laboratory Raman spectrometer equipped with a 532 nm laser.…”
Section: Raman Spectroscopy In Assessment Of Changes During Growth As...mentioning
confidence: 99%
“…Martin et al [ 85 ] developed a tomato ripening model based on vibrational bands of carotenoids in Raman spectra. Tomato fruit during the growth phase and during the post-harvest ripening stage were analysed using a laboratory Raman spectrometer equipped with a 532 nm laser.…”
Section: Raman Spectroscopy In Assessment Of Changes During Growth As...mentioning
confidence: 99%
“…The work done by Nikbakht and co-workers also showed that RS can be highly effective in quality assessment of both external and internal properties of tomatoes (Nikbakht et al, 2011). Martin and co-workers further expanded the use of RS for the analysis of tomatoes ripening (Martin et al, 2017). The researchers developed a model of tomato ripening based on carotenoid vibrational bands in Raman spectra.…”
Section: Fruit and Seed Quality Control Enabled By Raman Spectroscopymentioning
confidence: 99%
“…It has been found that an increase in carotenoid vibrations were coincident with the onset of the turning stage of the fruit ripening. The model built from the collected data describes the tomato ripening stages and helps to accurately assess postharvest fruit quality control (Martin et al, 2017).…”
Section: Fruit and Seed Quality Control Enabled By Raman Spectroscopymentioning
confidence: 99%
“…Since the maturation process of tomatoes has been studied intensely [30,31,39], 30 hot peppers were compared to the same number of tomatoes. Each species was represented by 10 fruits of the categories immature, maturing and fully matured fruits, see Table 1.…”
Section: Variabilities Of the Raman Band Intensitiesmentioning
confidence: 99%
“…Green or yellow harvested fruits also turn red when adequately stored and allowed to continue ripening. Since the degree of ripeness is related to the nutrients and to the carotenoid content, Raman spectroscopy is particularly suitable for monitoring of the process [29][30][31][32][33][34]. It provides good sensitivity to carotenoids and is non-invasive, such that the fruit can continue to evolve after analysis.…”
Section: Introductionmentioning
confidence: 99%